Processing and thermal properties of mayenite electride. Issue 5 (25th January 2021) - Mackey, Jon; Back, Tyson; Berger, Marie‐Hélène; Sayir, Ali
Abstract: A mayenite‐based electride is being considered for field emitter applications where it will be critical to have a good understanding of processing repeatability and thermal properties. This paper focuses on the details of processing of mayenite compounds in a strongly reducing graphite environment to form an electride solid‐solution phase as Ca12 Al14 O32 (C2, O2 )1‐x (e2 )x . The work reports, in addition to processing details, several thermal properties. The electride phase was found to have coefficient of thermal expansion (CTE) of 7e‐6 K −1, thermal diffusivity between 0.0063 and 0.0102 cm 2 /s, and thermal conductivity between 1.9 and 3.1 W m −1  K −1 . Rattling motion of O 2− or C2 2− ions in cage structure has been suggested to explain low thermal conductivity of the electride phase.